ANALYSIS OF IMPORTANT, CAREFUL, CERTAIN AND MUTUALLY AGREEABLE CRITERIA IN THE REGULATION OF ARTICLE 173 OF THE HERZIEN INLANDSCH REGLEMENT REGARDING EVIDENCE OF JUDGES' SUSPECTS - Naufal Anfasa Firdaus; Yenny Eta Widyanti; Rachmi Sulistyarini (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The sentence in Article 173 HIR which states "important, thorough, certain and mutually agreeable" is a regulation that is still abstract and can be interpreted in many ways, where this is like what category of important or very important circumstances are, then what is thorough or precise, how to assess certain conditions, and whether they correspond to each other whether they should be applied to 2 (two) types of evidence or what. The purpose of this study is to analyze the criteria contained in the sentence important, thorough, certain and mutually agreeable in the regulation of Article 173 HIR. The research method used is legal research with a statutory regulatory approach, a conceptual approach, and a case approach. Based on the research that has been carried out, it is known that normatively the criteria "important, thorough, certain and mutually agreeable" in Article 173 HIR are not explained completely, then after a theoretical analysis through the doctrines of legal experts and linguistically, namely Indonesian and legal language, the meaning contained therein is obtained. The "important" criterion contains relevant and logical boundaries directly related to the subject matter of the case, the "thorough" criterion contains methodological boundaries for the application of caution, the "certain" criterion contains specific boundaries and the strength of the evidence is not questioned, and the "mutually agreed" criterion contains for consistency and mutually corroborating evidence.